Synthesis, Characterization, and In Vitro Cytotoxicity of Platinum(II) Complexes Bearing Chiral Tetradentate Salicylaldimine Ligands - Quang Trung Nguyen; Phuong Nam Pham Thi; Van Tuyen Nguyen (Journal of Chemistry)
A series of platinum(II) complexes with chiral Schiff base ligands derived from various salicylaldehydes with (R,R′)- and (S,S′)-cyclohexanediamine were synthesized and characterized by ESI-MS, IR, and NMR. Obtained spectra with typical signals were in agreement with suggested molecular formulae of the complexes. Their photophysical properties were studied by UV-visible and emission spectroscopies. The UV-Vis showed the typical band with low energy at visible range 400–500 nm for MLCT, and this band can emit the luminescent band with emission maximum wavelengths at 529–595 nm. The in vitro cytotoxicity of obtained platinum(II) complexes was screened for KB and MCF-7 human cancer cell lines. The results showed that (S)-enantiomers were more active than (R)-enantiomers and the different positions of methoxy group in salicyl ring gave different cytotoxicities.